PEMBELAJARAN BINA KOMUNIKASI PERSEPSI BUNYI DAN IRAMA (BKPBI ) BAGI ANAK TUNARUNGU KELAS III SDLB - B DI SLBN - B GARUT - Haryati, Veronika Siti (2015)
Linguistic activities, either spoken, written, or with sign, play a key role in the teaching and learning process. Meanwhile, hearing-impaired children are very limited in their speech and linguistic development because the children do not go through the sound imitation process after the stage of babbling; hence, communication development through sound and rhythm perception (henceforth, BKPBI), which is an activity of optimizing hearing-impaired children's hearing, is very important. The research reveals how BKPBI for the third grade SDLB hearing-impaired students is implemented in SLBN B Garut, adopting descriptive-qualitative method. Data were collected with the techniques of observation, interview, and documentation of teacher-1, teacher-2, and four students. Data validity was tested with triangulation technique. Research results show that before making lesson plans, the two teachers under research conduct assessment, but still limited to listening skills. The components included in the lesson plans have been in accordance with the standard process; and the stages of implementation, starting from preliminary, main, and closing activities, have been relevant to the standard process as well. However, the first teacher only teaches up to the level of comprehending man-made background sounds, while linguistic sound comprehension is developed through the teaching and learning of articulation. Meanwhile, in addition to teaching man-made background sound comprehension, the second teacher also teaches linguistic sound comprehension with the so-called "berperdati" technique. Evaluation is conducted in two ways, namely through observation on students' concentration and responses during the teaching and learning process, and the cognitive, affective, and psychomotor assessment on learning outcomes. Finally, the efforts made to solve difficulties, such as teachers' low competence in assessment, limited availability of media and learning resources for music and BKPBI, and the lack of support from parents, consist of proposing training programs, provision of learning media and resources, as well as school benchmarking and counseling for parents on the importance of BKPBI. Keywords: BKPBI Teaching and Learning, Hearing-Impaired Children, Special Needs School Kegiatan berbahasa baik lisan, tulisan maupun isyarat memegang peran penting dalam segala kegiatan pembelajaran, sementara pada anak tunarungu terganggunya ketajaman pendengaran sangat menghambat perkembangan bicara dan bahasa, karena pada anak tunarungu tidak terjadi proses peniruan suara setelah proses meraban sehingga BKPBI yang merupakan kegiatan untuk mengoftimalkan fungsi pendengaran bagi anak tunarungu, sangat penting dilaksanakan. Penelitian ini mengungkap bagaimana pelaksanaan pembelajaran BKPBI bagi anak tunarungu kelas III SDLB di SLBN B Garut, menggunakan metode deskriptif kualitatif. Teknik pengumpul data yang digunakan adalah observasi, wawancara, dan dokumentasi terhadap guru-1, guru-2 dan empat orang siswa. Pengujian keabsahan data menggunakan teknik triangulasi. Hasil penelitian menunjukan bahwa sebelum menyusun RPP kedua orang guru melaksanakan assesmen tetapi masih terbatas dalam lingkup listening skill. Komponen yang dituangkan dalam RPP sesuai dengan dengan standar proses, tahapan pelaksanaan pembelajaran baik kegiatan awal, inti dan akhir, sudah relevan dengan standar proses pembelajaran tetapi guru-1 terbatas hanya mengajarkan materi sampai pada taraf penghayatan bunyi latar belakang buatan manusia sementara penghayatan bunyi bahasa dikembangkan dalam pembelajaran artikulasi dan guru-2 disamping mengajarkan penghayatan bunyi latar belakang buatan manusia juga mengajarkan penghayatan bunyi bahasa dengan teknik berperdati . Evaluasi dilakukan dalam dua tahap yaitu evaluasi proses berupa pengamatan terhadap konsentrasi dan respon siswa selama proses pembelajaran berlangsung serta evaluasi hasil belajar berupa penilaian kognitif, afektif dan psikomotor. Upaya yang dilakukan dalam mengatasi kesulitan berupa: rendahnya kompetensi guru dalam bidang asesmen, musik serta BKPBI juga terbatasnya alat dan sumber belajar serta kurangnya dukungan orang tua adalah mengajukan pelatihan, kelengkapan alat dan sumber serta study banding kepada pihak sekolah serta melakukan konseling tentang pentingnya BKPBI terhadap orang tua. Kata Kunci : Pembelajaran BKPBI, Anak Tunarungu, SLB